2015
DOI: 10.1128/jvi.02742-14
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi's Sarcoma-Associated Herpesvirus Induces Nrf2 Activation in Latently Infected Endothelial Cells through SQSTM1 Phosphorylation and Interaction with Polyubiquitinated Keap1

Abstract: Nuclear factor erythroid 2-related factor 2 (Nrf2), the cellular master regulator of the antioxidant response, dissociates from its inhibitor Keap1 when activated by stress signals and participates in the pathogenesis of viral infections and tumorigenesis. Early during de novo infection of endothelial cells, KSHV induces Nrf2 through an intricate mechanism involving reactive oxygen species (ROS) and prostaglandin E2 (PGE2). When we investigated the Nrf2 activity during latent KSHV infection, we observed increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 106 publications
(157 reference statements)
2
45
0
Order By: Relevance
“…To assess the effect of IFI16 KD on TPA-mediated KSHV lytic reactivation, BCBL-1 cells were transduced with a lentivirus containing ShIFI16 or a control lentivirus. Forty-eight hours later, cells were induced with TPA (20 ng/ml), and total RNA was isolated after 0, 3,6,9,12,24,36,48,72, and 96 h, as indicated (Fig. 3A).…”
Section: Ifi16 Knockdown In Pel Cells Results In Global Increasesmentioning
confidence: 99%
See 2 more Smart Citations
“…To assess the effect of IFI16 KD on TPA-mediated KSHV lytic reactivation, BCBL-1 cells were transduced with a lentivirus containing ShIFI16 or a control lentivirus. Forty-eight hours later, cells were induced with TPA (20 ng/ml), and total RNA was isolated after 0, 3,6,9,12,24,36,48,72, and 96 h, as indicated (Fig. 3A).…”
Section: Ifi16 Knockdown In Pel Cells Results In Global Increasesmentioning
confidence: 99%
“…At 72 h postinfection (p.i. ), when latency is established (47), cells were treated with TPA or a vehicle control for 2, 3, and 4 days (48,72, and 96 h), and IFI16 levels were determined by WB analysis. As a control, mock-infected cells were also treated with TPA to rule out any off-target effects of TPA on IFI16 levels (Fig.…”
Section: Ifi16 Knockdown In Pel Cells Results In Global Increasesmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that both EBV and KSHV might be able to express the cell survival factor NRF2 in infected cells at least at the RNA level. In the case of KSHV, it was demonstrated and seemed to be important that the latent KSHV protein, vFLIP (Fas-associated death domain-like IL-1-converting enzyme-inhibitory protein) increased SQSTM1 expression and led to stabilization of NRF2 [107]. Thus, KSHV could dually activate the NRF2 pathway during oncogenesis by hijacking canonical NOTCH signaling transcriptionally and manipulating the autophagic pathway of KEAP1 degradation through induction of SQSTM1 post-translationally ( Figure 5B).…”
Section: Dark Side Of Activation Of Both Signaling Pathways (Oncogenementioning
confidence: 99%
“…In a set of recent studies, we demonstrated that de novo KSHV infection of endothelial cells induced Nrf2 through multiple mechanisms to create a microenvironment conducive to infection (30,32). In the current study, we further investigated the role of Nrf2 in KSHV gene expression, focusing mainly on latently infected, PEL-derived cell lines.…”
mentioning
confidence: 93%